User-Generated Content, Online Trust, and Purchase Intention: An Empirical Study of Social Commerce Platforms - Nguyen Van Dat; Canh Chi Hoang; Bui Thanh Khoa (Jurnal the Messenger, 2025)
Purpose: User-generated content (UGC) affected consumer trust and purchasing intention in social commerce platforms. It evaluated the growing influence of user-generated content on online consumer behavior and how online trust mediates the association between UGC and purchase intention. This study intended to understand how different types of UGC affect consumer trust and buy intentions, moving beyond previous studies' focus on individual UGC parts.